Antioxidant and antimicrobial properties of dried Portuguese apple variety (Malus domestica Borkh. cv Bravo de Esmolfe) - Pires, Tânia C.S.P.; Dias, Maria Inês; Barros, Lillian; Alves, Maria José; Oliveira, M. Beatriz P.P.; Santos-Buelga, Celestino; Ferreira, Isabel C.F.R. (Food chemistry, 2018)
•Apple fruits are rich sources of palmitic acid, α-tocopherol, fructose and malic acid.•Epicatechin and B-type procyanidins were the main phenolic compounds found.•Hydroxycinnamoyl-quinic acids and phloretin derivatives were also found.•Hydromethanolic extracts proved to have antioxidant and antibacterial capacity. Malus domestica Borkh apples are one of the most consumed fruits in the world, due to their sweetness and flavour. Herein, ‘Bravo de Esmolfe’ apple fruits were characterized regarding their nutritional value, chemical composition and bioactive properties. Besides nutrients, flavan-3-ols (i.e., epicatechin and B-type procyanidins) as also hydroxycinnamoyl-quinic acids and phloretin derivatives were identified in the samples. Extracts prepared from ‘Bravo de Esmolfe’ also proved to have antioxidant activity and antibacterial effects against Gram-positive bacteria, namely methicillin-susceptible Staphylococcus aureus (MSSA), methicillin-resistant Staphylococcus aureus (MRSA), Listeria monocytogenes and Enterococcus faecalis, and against the Gram-negative bacteria Escherichia coli, Escherichia coli (ESBL) (producing extended spectrum β-lactamases) and Morganella morganii. There is very little information about ‘Bravo de Esmolfe’ apple, so this study is important to inform consumers about an alternative source of nutritional and bioactive compounds.